'It's the unknown' – understanding anxiety: from the perspective of people with multiple sclerosis. Issue 3 (4th March 2019) - Butler, Ellen; Thomas, Reena; Carolan, Alison; Silber, Eli; Chalder, Trudie
Abstract: Objective: A qualitative study of PwMS who had clinically significant levels of anxiety was conducted to gain a richer perspective on their experience. The objective was to explore PwMS' experiences of anxiety and their perspectives on causes and outcomes.Design: Twenty in-depth, semi-structured interviews were conducted with PwMS consecutively recruited from the Neurology Department of a NHS University Hospital. Sixteen had a relapsing-remitting course, three had a secondary progressive course and one person had primary progressive multiple sclerosis (MS). Interviews were recorded, transcribed and analysed using inductive thematic analysis.Results: Although participants thought different factors had initially triggered their anxiety, being given the diagnosis of MS appeared to be the most significant factor for many participants. Difficulties in the workplace and in relationships, particularly related to perceived dependence on others were also important themes. A wide range of emotional responses and negative thinking patterns were associated with anxiety; this suggested the presence of comorbid depression. Participants were able to acknowledge the positive and negative coping strategies that impacted on their anxiety.Conclusion: This review confirms that anxiety can have many negative implications for PwMS and suggests that early detection and intervention are necessary in order to improve patient's well-being.